Penerapan Model Pembelajaran Jigsaw untuk Meningkatkan Hasil Belajar Sains pada Siswa Kelas V SD GMIM III Tomohon - Fransisca G. Palendeng; Amiana M. Mogot; Magdalena Kaunang; Fransisca Korompis; Yusak Ratunguri (Peneliti.net, 2022)
This study aims to improve learning outcomes and improve teaching and learning activities in science learning about the force of gravity. For this purpose, the researchers studied more deeply about the application of the Jigsaw model in gravity science subjects to improve learning outcomes for fifth grade students of SD GMIM III Tomohon. The research method used is Classroom Action Research (CAR) which is carried out in two cycles, consisting of 4 stages, namely planning, action, observation, and reflection. data collection through observation sheets and tests. This research is said to be successful if it reaches the success indicator with 80% completeness. Student learning outcomes in science subjects on the gravity force material, have increased after being implemented using the Jigsaw learning model. In the first cycle the results achieved were 58% and in the second cycle the results were 86%. So in conclusion, with the application of the Jigsaw model, there was an increase in the learning outcomes of fifth graders at SD GMIM III Tomohon.